Design Of Edc Machine Case And Stand Using House Of Quality And Anthropometry Measurement - et. al., Verani Hartati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Non-cash transactions using an electronic data capture (EDC) machine is a normal thing that happens in a store (merchant), the primary users are between the cashier and the customer. EDC which is widely used in Indonesia is only able to accept non-cash payments from one bank or payment channel, resulting in shops having to provide various types of EDC machines from various banks. PT TX plans to make EDC with the latest features that can accommodate non-cash payments from various banks and payment channels, so an ergonomic EDC case design is required. The research objective was to design an EDC case according to the needs of potential users. . The method used is the House of Quality (HoQ) because this method can process the customer requirements into a correlated technical response to help the EDC case design process. Also, the anthropometric approach is used to realize an ergonomic product design, namely using the dimensions of the eye height. Data processing using HoQ shows that the design attributes of the shape and size dimensions of the product are the attributes with the highest-ranking, and become the main technical sponge that must be focused on in designing the EDC machine case and stand. From anthropometric data processing obtained information regarding the amount of the angle of inclination for customer display is 25 degrees. The resulting product design has considered customer requirements and ergonomic principles in product design, thus it is expected to meet user satisfaction.